Enhancing Serials Holdings Data: A Pymarc-Powered Clean-Up Project - Minyoung Chung and Phani Chaitanya Pendyala (Code4Lib Journal)
Following the recent transition from Inmagic to Ex Libris Alma, the Technical Services department at the University of Southern California (USC) in Los Angeles undertook a post-migration cleanup initiative. This article introduces methodologies aimed at improving irregular summary holdings data within serials records using Pymarc, regular expressions, and the Alma API in MarcEdit. The challenge identified was the confinement of serials' holdings information exclusively to the 866 MARC tag for textual holdings. To address this challenge, Pymarc and regular expressions were leveraged to parse and identify various patterns within the holdings data, offering a nuanced understanding of the intricacies embedded in the 866 field. Subsequently, the script generated a new 853 field for captions and patterns, along with multiple instances of the 863 field for coded enumeration and chronology data, derived from the existing data in the 866 field. The final step involved utilizing the Alma API via MarcEdit, streamlining the restructuring of holdings data and updating nearly 5,000 records for serials. This article illustrates the application of Pymarc for both data analysis and creation, emphasizing its utility in generating data in the MARC format. Furthermore, it posits the potential application of Pymarc to enhance data within library and archive contexts.